Is Olfactory Impairment Associated With 10-year Mortality Mediating by Neurodegenerative Diseases in Older Adults? The Four-Way Decomposition Analysis - Cao, Yang; Xiao, Zhenxu; Wu, Wanqing; Zhao, Qianhua; Ding, Ding (Frontiers in Public Health, 2021)
Background: Literature shows that olfactory impairment (OI) is associated not only with neurodegenerative diseases (NDDs), but also with increased mortality. In the current study, we analyzed data collected from the prospective phase of the 10-year follow-up of the Shanghai Aging Study (SAS), to explore the mediation effect of NDDs on the OI-mortality relationship. Methods: We analyzed data collected from the prospective phase of the 10-year follow-up of the SAS. We included 1811 participants aged 60 years or older who completed both an olfactory identification test and a cognitive assessment at baseline (2010-2011). Survival status of the participants from baseline to December 31, 2019 were obtained from the local mortality surveillance system. We used the four-way decomposition method to attribute effects to interaction and mediation, and to explore the mediation effect of NDDs on the OI-mortality relationship. Results: The four-way decomposition revealed a statistically significant association of OI with death. Overall, 43% higher risk for death was associated with OI [excess relative risk (ERR) = 0.43, 95% CI: 0.06–0.80, p = 0.023]. Excluding the mediation from NDDs and interaction between OI and NDDs, the controlled direct effect of OI on death was even higher in NDDs participants, with an ERR of 77% (95% CI: 0.00 – 1.55, p = 0.050). Statistically significant association was found for failure to identify coffee (ERR = 0.77, 95% CI: 0.18 – 1.36, p = 0.010) and marginally significant associations were found for failure to identify cinnamon (ERR = 0.33, 95% CI: -0.02 – 0.68, p = 0.068) and rose (ERR = 0.33, 95% CI: -0.01 – 0.67, p = 0.054) with death. Conclusion: OI was associated with the long-term mortality in older adults, and the association was even stronger in those with NDDs. Failure to identify coffee or rose, was associated with a higher mortality risk, and the association was mediated by NDDs.